1987
DOI: 10.1002/jlb.42.3.181
|View full text |Cite
|
Sign up to set email alerts
|

Rat Monocytes in a Model of Combined Injury Express the OX8 Antigen

Abstract: We have analyzed peripheral blood mononuclear cell preparations from a rat model of combined injury (CI) [whole-body irradiation (500 cGy 60Co) followed by a thermal injury (20% body surface area, dorsal, scald burn)] for the expression of OX8 antigens. Ficoll-separated mononuclear fractions were labeled with monoclonal antibodies MRC OX8, MRC OX19, W3/13 HLK, or W3/25 for flow cytometric analysis. Combined-injury trauma resulted in decreased mononuclear cells to 6% of normal. This effect was due to the rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Whether the b-chain was also present could not be assessed as MoAb 341 gave equivocal staining results. There is increasing evidence that CD8 may occur in cells other than T cells and NK cells, and a population of Ox8-positive monocytes has been detected by flow cytometry in a rat model of sublethal total-body irradiation followed by thermal injury [55]. In addition, rat Kupffer cell precursors [51], a subpopulation of tumour-infiltrating dendritic cells in rats [56], certain dendritic cells in the thymus and spleen of normal mice [57,58] and peritoneal as well as alveolar macrophages [59] express the CD8 antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the b-chain was also present could not be assessed as MoAb 341 gave equivocal staining results. There is increasing evidence that CD8 may occur in cells other than T cells and NK cells, and a population of Ox8-positive monocytes has been detected by flow cytometry in a rat model of sublethal total-body irradiation followed by thermal injury [55]. In addition, rat Kupffer cell precursors [51], a subpopulation of tumour-infiltrating dendritic cells in rats [56], certain dendritic cells in the thymus and spleen of normal mice [57,58] and peritoneal as well as alveolar macrophages [59] express the CD8 antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that CD8␣ protein is expressed by NK cells in rat [27] and human [28] but not in mouse [29] ( Table 1 and references therein). Similarly rat [42,44] and human monocytes [31] and macrophages [35] express CD8␣, and the same cells in the mouse lack CD8␣ [33]. Intriguingly, rat macrophages and mast cells also express CD8␤ [35,36].…”
Section: Cell Types That Express Cd8 and Cd4 Vary Among Mammalian Spementioning
confidence: 99%
“…Large numbers of CD8 ϩ macrophages and monocytes have been observed in several models of disease in rats, including glomerulonephritis [102], arthritis [103], ischemia [104], severe trauma [44], transplant rejection [42], experimental allergic encephalomyelitis [105], autoimmune thyroid disease [106], myocarditis [5], viral infection [107], and tumors [3]. CD8 ϩ monocytes increase proportionally after induction of several of these diseases, express markers associated with cytotoxicity [5], and localize to sites of tissue destruction [102], suggesting that they may have an active role in causing tissue pathology.…”
Section: A Role For Cd8 In Cytotoxic Responses Of Monocytes and Macromentioning
confidence: 99%
“…1 It has been reported that monocytes may be induced to express OX8 in vivo [24]. In our laboratory, lymphocyte-depletion studies with monoclonal antibody OX8 given intraperitoneally resulted in a significant reduction in circulating monocyte numbers [unpubl.…”
Section: Renal Immunofluorescence Studiesmentioning
confidence: 99%
“…The pattern of reactivity of these antibodies is summarized in table I [for a more detailed discussion, see ref. [18][19][20]24].…”
Section: Characterization O F Interstitial Cellsmentioning
confidence: 99%